2013
DOI: 10.1017/s1092852913000862
|View full text |Cite
|
Sign up to set email alerts
|

Stroop task among patients with obsessive-compulsive disorder (OCD) and pathological gambling (PG) in methadone maintenance treatment (MMT)

Abstract: MMT patients had generally poorer performance, as indicated by longer RTs, that were related to clinical OCD, drug abuse, poor cognitive state, and older age. Patients with both clinical OCD and ADHD had a higher Stroop interference effect, which is a reflection of an attention deficit. In order to improve clinical approach and treatment of MMT patients, OCD and ADHD should be evaluated (and treated as needed).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 44 publications
(78 reference statements)
2
1
0
Order By: Relevance
“…Attentional inhibition, which refers to the ability to sustain attention for task-relevant information while inhibiting responses to irrelevant information, is an important aspect of cognitive inhibition and is thought to play a central role in the etiology of OCD (Harnishfeger, 1995;Bannon et al, 2002;Putman et al, 2012;Chamberlain et al, 2005). Many studies have confirmed a deficit in cognitive inhibition in OCD patients (Penades et al, 2007;Peles et al, 2013;Lei et al, 2013) and our results may also dovetail with the cognitive inhibition deficit model of OCD. In our study, deficit inhibition was common to all three types of words, which indicates that inhibition dysfunction in OCD may not be related to emotional valence-an interpretation that fits with the work of Waters and Farrell (2014).…”
Section: Discussionsupporting
confidence: 80%
“…Attentional inhibition, which refers to the ability to sustain attention for task-relevant information while inhibiting responses to irrelevant information, is an important aspect of cognitive inhibition and is thought to play a central role in the etiology of OCD (Harnishfeger, 1995;Bannon et al, 2002;Putman et al, 2012;Chamberlain et al, 2005). Many studies have confirmed a deficit in cognitive inhibition in OCD patients (Penades et al, 2007;Peles et al, 2013;Lei et al, 2013) and our results may also dovetail with the cognitive inhibition deficit model of OCD. In our study, deficit inhibition was common to all three types of words, which indicates that inhibition dysfunction in OCD may not be related to emotional valence-an interpretation that fits with the work of Waters and Farrell (2014).…”
Section: Discussionsupporting
confidence: 80%
“…High YBOCS scores have been associated with an impaired Stroop Test performance in this study. Our result is consistent with the study of Peles, which declared that a Stroop Test interference was correlated significantly with the OCD severity score 43 . Contradictory to this finding, Nielen reported that cognitive impairments could be a trait feature because they detected that cognitive symptoms were not secondary to symptoms 22 .…”
Section: Discussionsupporting
confidence: 93%
“…Exclusion criteria included age above 55 and positive urine for any drugs in the last 3 months. Participants were randomly tested before or after methadone administration (Peles et al, 2013), with 15-120 min interval (average time = 57.6 ± 28.4 min) between administration and testing for those who were tested after methadone administration. The experiment was done in accordance with the Declaration of Helsinki for the protection of human participants (Tel Aviv Sourasky Medical Center Ethics, IRB number 251-13).…”
Section: Participantsmentioning
confidence: 99%